Principles and Parameters of the Orthodox Financial System as an Element of the Orthodox Economy and the “Church-State” Relations – State Intervention or “Symphonic Concept” of Cooperation - Iliev, Petkan (Research Papers, 2022)
In the present study we will focus on the analysis of religious activity in its socio-economic aspect in terms of the principles and parameters of the Orthodox financial system. At the same time, the typology of the relationship between church and state is extremely diverse, but specifically for the Orthodox religion it is identified with the so-called “symphonic concept”.
Keywords: Church economy; Church; Orthodox economy; Bulgarian orthodox church; Religious activity